Sonographic measurements of the achilles tendon, plantar fascia, and heel fat pad are reliable: A test‐retest intra‐ and intertester study. Issue 8 (7th May 2016) - Johannsen, Finn; Jensen, Signe; Stallknecht, Sandra E.; Olsen, Lars Otto; Magnusson, S. Peter
ABSTRACT: Purpose: To determine intra‐ and interobserver reliability and precision of sonographic (US) scanning in measuring thickness of the Achilles tendon, plantar fascia, and heel fat pad in patients with heel pain. Methods: Seventeen consecutive patients referred with heel pain were included. Two evaluators blinded to the diagnosis performed independently US scanning of both feet without any dialogue with the patient. The examiner left the room, and the next examiner entered. All patients had two US scans performed by each examiner. Two months later, the US images were randomly presented to the evaluators for measurements. Reliability and agreement were assessed by calculation of intraclass correlation coefficient (ICC), 95% limits of agreement (LOA), and typical error (TE). LOA was calculated as a percentage of the mean thickness of each structure to obtain a unitless parameter. Results: We found excellent intratester reliability (ICC 0.78–0.98) and good intertester reliability using one measurement (ICC 0.72–0.91) and excellent (ICC 0.85–0.95) when using average of two measurements. The intratester agreements were good with LOA: 9.5–23.4% and TE: 3.4–8.4%. The intertester agreements were acceptable using one measurement with LOA: 16.1–36.4%, and better using two measurements with LOA: 14.4–33.2%. Conclusions: US is a reliable technique of measurement in the daily clinic, and one single measurement is sufficient. In research, we recommend that the same observer performs the US measurements, if one single scanning is preferred; if more researchers are involved, the average measurement of two US scans is recommended. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 44 :480–486, 2016